THE CORRELATION BETWEEN STUDENTS’ VOCABULARIY MASTERY AND THEIR ENGLISH READING PROFICIENCY - SURYATI (JEE (Journal of English Education), 2015)
This study discussed about the correlation between vocabulary mastery and their English reading proficiency. The researcher’s interest on her classroom instruction became the background of this research. By determining descriptive correlational model as the research design, the research got the answer of how students’ vocabularies contribute their English reading proficiency. After collecting and analyzing the data gained from vocabulary test and reading proficiency test, it could be concluded that there was a significant correlation between English vocabulary mastery and Reading proficiency of the second year student of SMPN 05 Tambusai Utara.